2023
DOI: 10.3390/nu15163523
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability in Patients with Type 2 Diabetes Mellitus (T2DM): The Role of Melatonin in a Crossover, Double-Blind, Placebo-Controlled, Randomized Study

Abstract: Background: Glycemic variability in patients with type 2 diabetes mellitus (T2DM) may be associated with chronic complications of the disease. Melatonin is a hormone that plays a crucial role in biological rhythms. Previous studies have indicated that individuals with T2DM often exhibit reduced melatonin production. In this study, our objective was to investigate whether nighttime melatonin supplementation could mitigate glycemic variability in these patients. Methods: Crossover, double-blind, placebo-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…One study enrolled 30 patients with type 2 diabetes and gave them melatonin therapy for 7 days. The results showed that melatonin supplementation increased glycemic variability in patients with T2DM (Martorina and Tavares, 2023). However, some studies have suggested that melatonin is effective in treating diabetes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One study enrolled 30 patients with type 2 diabetes and gave them melatonin therapy for 7 days. The results showed that melatonin supplementation increased glycemic variability in patients with T2DM (Martorina and Tavares, 2023). However, some studies have suggested that melatonin is effective in treating diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, we found that energy metabolism imbalance was the main cause of diabetes-induced hippocampal damage, including carbon metabolism (TCA cycle, glycolysis/gluconeogenesis, pyruvate metabolism), purine metabolism, biosynthesis of amino Correlation analysis of DEPs-DRMs showed that melatonin may be a critical target for DP to alleviate DCI. Abnormal melatonin secretion affects blood glucose levels (Martorina and Tavares, 2023) and circadian rhythm. Hyperglycemia and circadian rhythm disorder are risk factors for DCI (Barone et al, 2021;Liu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%